PROCESSING, MICROSTRUCTURE AND MAGNETIC PROPERTIES OF ALNICO RIBBONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
Alnico alloys are known as nanostructured metallic magnets, having good corrosion and thermal stability, many research is devoted to finding a miniaturization solution of this kind of permanent magnet in order to gain magnetic properties suitable to replace the permanent magnets containing critical elements, like Sm-Co and Nd-Fe-B permanent magnets, in the devices that require lower performances and not so expensive routes for processing.The experiments consisted of the preparation of ribbons samples from Alnico-based alloy processed in an induction furnace. From the obtained ingot, there were process ribbons by melt-spinning technique. The obtained ribbons were then heat-treated and characterized through X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). The coercivity of the as-spun ribbons was enhanced from 16.92 kA/m to 32.57 kA/m after heat treatment.A squareness ratio of around 0.6 is due to the minor crystalline phases and to the residual stress induced by the rapid solidification process of the 2D structure of the ribbons, indicating a good candidate for radio-frequency identification (RFID), micro-electro-mechanical systems (MEMS), and other applications such as microwave circulators.
Keywords: Alnico; Ribbons; Melt-spinning; Free-rare earth permanent magnets; Nanostructured alloy